CHARACTERISTICS OF CELL SMEARS OF LINGUAL BACK IN THE PRESENCE OF PLATE DENTURES - Семенова, А.К.; Єрошенко, Г.А.; Tsukanov, D.V. (World of Medicine and Biology, 2015)
The article presents the results of a comprehensive cytology reactive changes back Yazikov cellular composition of human beings in the presence of oral lamellar dentures. During the study shows that the qualitative changes in epithelial cells in the form of restructuring proyavlyayutsya tinctorial properties of the components of the cytoplasm of intermediate and superficial cells. This changes the coloring in different shades of purple and define by numerous vacuolar inclusions and tablyudaetsya uzuratsiya plazmolemy contours. Cyto-morphological picture, by increasing the number of horny scales shows a strong tendency to hyperkeratosis Roswitha ─ Increase in individuals epidermidalization local population.
Keywords: cellular structure; the epithelium; vacuolation